Edukasi Kesehatan Reproduksi Berbasis Syariah Efektifitas Meningkatkan Sikap Dalam Pendewasaan Perkawinan - Chika Putri Permata Amelia; Sri Wahyuni; Tutik Rahayu (Journal of Innovative and Creativity, 2026)
Early marriage before the age of 18 has negative impacts on adolescent reproductive health, while the coverage of family empowerment programs like PIK-R remains limited. This study aims to assess the effectiveness of sharia-based reproductive health education via video on adolescents' attitudes toward marriage age maturity in Semarang City. Using a quasi-experimental design with 100 respondents (50 per group) selected through purposive sampling, data were collected via questionnaires and analyzed using Wilcoxon and Mann-Whitney tests. The results showed that the majority of respondents were 17 years old (73%), female (61%), and had two siblings (54%). In the intervention group, positive attitudes increased significantly from 48% to 74% after the intervention (p = 0.000), while the control group showed no significant change (p = 0.271). The Mann-Whitney test confirmed the effectiveness of the education with p = 0.001. In conclusion, sharia-based reproductive health education is effective in improving adolescents' positive attitudes toward marriage age maturity, and its implementation in schools is recommended as a preventive measure against early marriage.